2010
DOI: 10.1111/j.1469-8137.2010.03500.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide participates in cold‐responsive phosphosphingolipid formation and gene expression in Arabidopsis thaliana

Abstract: Summary• Chilling triggers rapid molecular responses that permit the maintenance of plant cell homeostasis and plant adaptation. Recent data showed that nitric oxide (NO) is involved in plant acclimation and tolerance to cold. The participation of NO in the early transduction of the cold signal in Arabidopsis thaliana was investigated.• The production of NO after a short exposure to cold was assessed using the NOsensitive fluorescent probe 4, 5-diamino fluoresceine diacetate and chemiluminescence. Pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
209
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(239 citation statements)
references
References 43 publications
17
209
2
1
Order By: Relevance
“…This fact is supported because an increase in NO production has been generally reported when plants were subjected to stresses [97]. For example, drought-induced NO production has been reported in many plant species, including pea, wheat and tobacco [98].…”
Section: Effect Of No On Plant Growth Responses Under Drought and Salsupporting
confidence: 56%
“…This fact is supported because an increase in NO production has been generally reported when plants were subjected to stresses [97]. For example, drought-induced NO production has been reported in many plant species, including pea, wheat and tobacco [98].…”
Section: Effect Of No On Plant Growth Responses Under Drought and Salsupporting
confidence: 56%
“…Signal molecules are involved in perception and transduction of low temperature signal and mediate chilling adaptive responses through physiological processes and transcription factors [17][18][19][20]. Recent research indicated that multiple transcription factors and inducers, such as C-repeat-binding factor (CBF), inducers of CBF expression (ICE) and cold-regulated (COR) genes, played pivotal roles in the resistance to low temperature stress [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The NR activity reducing also influences nitrogen metabolism. NR activity is related to the peroxidation of plant membrane lipids [40]. After the SNP treatment at different concentrations, the NR activity was significantly elevated under enhanced UV-B radiation.…”
Section: Discussionmentioning
confidence: 99%